Dampak Lalu Lintas Pada Kawasan Pembangunan Lintas Bawah (Underpass) Simpang Surabaya, Banda Aceh - Utami, Cut Sabrina; Sugiarto, Sugiarto; Saleh, Sofyan M. (Journal of The Civil Engineering Student, 2025)
Most urban areas are suffering from unmaintained externalities such as excessive travel time, unnecessary fuel consumption and even serious economic loss due extraordinary growth in automobile traffic (i.e. motorcycle and car), and as consequence of automobile ownership and usage have continued rapid growth into recent days including in Banda Aceh, a capital of Aceh Province. An increasing of automobile usage led to induce traffic congestion in the city centers including in Surabaya Intersection. To counter the negative effects of the congestion, the Government of Aceh decided to build an Underpass road segment. However, during the construction, traffic congestion and loading randomly distributed in surrounding corridors nearby construction site. Therefore, this research aim to analyzed the impact of Underpass. The study was conducted at Jalan Teuku Daud Beureueh, Jalan Teuku Nyak Arief and Jalan T Hasan Dek. The findings from the analysised reveal that the traffic loading has been increased accounting up to 31%, 31% and 55% for Jalan Tgk. Daud Beureueh, Jalan T. Nyak Arief and Jalan T. Hasan Dek, respectively. Furthermore, the result of level of service (LOS) analysed shows that dropped in LOS from B to C during construction period for Jalan Tgk. Daud Beureueh, Jalan Teuku Nyak Arief and Jalan Teuku Hasan Dek.